MANAJEMEN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA GAYA HIDUP BERKELANJUTAN DI SEKOLAH MENENGAH PERTAMA NEGERI KABUPATEN KUTAI TIMUR - Helmina; Dwiyono, Yudo; Komariyah, Laili; Mulawarman, Widyatmike Gede; Azainil; Haryaka, Usfandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Sustainable living has become an essential concept in maintaining ecosystem balance and managing natural resources. One of the environmental issues frequently occurring around SMP Negeri 1 Long Mesangat is the uncontrolled growth of aquatic weeds, such as water hyacinth, which can disrupt the ecosystem. This study aims to describe the planning, organization, implementation, monitoring, and the relationship between sustainable living and aquatic weeds. The research findings indicate that:1)Planning involves identifying environmental issues in the school, setting objectives, designing the curriculum, drafting activity plans, analyzing resources, and determining success indicators.2)Organization includes forming a team, delegating tasks, providing facilities and infrastructure, and scheduling activities.3)Implementation consists of collecting, cleaning, and fermenting aquatic weeds for two weeks, extracting leachate, and drying the remaining plant material.4)Monitoring is carried out through teacher evaluations by comparing results with targets, as well as individual and group reflections to assess the project's impact on the environment and learning.5)Sustainable living and aquatic weeds are interconnected in environmental management, where excessive aquatic weeds caused by pollution can be productively utilized. This helps reduce waste, maintain the balance of aquatic ecosystems, and support recycling practices and sustainability.